Geochemical study on nitrogen isotope composition, speciation distribution, and influencing factors of vitrinite-rich coal seams during the Late Carboniferous - Dun Wu; Liu Zhao; Bo Li; Nyasha Ndhlovu Kataza (Scientific Reports)
Abstract This study focuses on Coals 8 and 9 of the Late Carboniferous Taiyuan Formation in the eastern part of the north China Craton Basin. Through comprehensive industrial analysis, XPS, and nitrogen isotope techniques applied to 16 collected coal samples, the distribution of nitrogen in coal and the differentiation mechanism of δ 15N values were revealed. The results indicate that most coal samples exhibit high ash content, high volatile matter, and ultra-low moisture. Nitrogen exists in an organic state, with N-5 dominating and N-6 being secondary. The δ 15N values range from 0.72 to 3.15‰ for Coal 8 and − 1.90 ~ − 0.38‰ for Coal 9, deviating from China’s typical range, with positive and negative differences between Coal 8 and 9. These isotopic differences are influenced by factors such as depositional environments and diagenesis. δ 15N shows a negative correlation with total nitrogen content and a close association with macerals (negative correlation with vitrinite and positive correlation with inertinite). The deep-water reducing environment in the east and the shallow marine environment at the southern margin play regulatory roles in nitrogen isotope fractionation. This study provides crucial geochemical evidence for the reconstruction of ancient depositional environments and the nitrogen cycling mechanisms during coalification processes.